Economics of Natural Resources, the Environment and Policies - Kula, E. (chapman & hall, 1994)
The economic activities of humanity, particularly during the last couple of cen turies, have had a profound impact on the natural environment. Fast depletion of the world's forest resources, fish stocks, fossil fuels and mine deposits have raised many moral as well as practical questions concerning present and future generations. Furthermore, a number of global environmental problems such as acid rain, the 'greenhouse effect' and depletion of the ozone layer are causing concern throughout the world.